Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1103/physrevb.94.035114
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field dependence of the neutron spin resonance inCeB6

Abstract: In zero magnetic field, the famous neutron spin resonance in the f-electron superconductor CeCoIn 5 is similar to the recently discovered exciton peak in the nonsuperconducting CeB 6 . A magnetic field splits the resonance in CeCoIn 5 into two components, indicating that it is a doublet. Here we employ inelastic neutron scattering (INS) to scrutinize the field dependence of spin fluctuations in CeB 6 . The exciton shows a markedly different behavior without any field splitting. Instead, we observe a second fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 53 publications
6
29
0
Order By: Relevance
“…It is worth noting that the FM component in CeB 6 was later confirmed in neutron scattering experiments910. Moreover, recent comparative study revealed an excellent agreement between the dispersion laws ω(B ) for the main gapless resonant mode in the AFQ phase subtracted from the ESR measurements and from the neutron scattering in magnetic field data11. This mode corresponding to the g -factor g  ~ 1.6–1.7 may be traced up to ω/2π ~ 350 GHz for magnetic field aligned along [110] crystallographic direction1112.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…It is worth noting that the FM component in CeB 6 was later confirmed in neutron scattering experiments910. Moreover, recent comparative study revealed an excellent agreement between the dispersion laws ω(B ) for the main gapless resonant mode in the AFQ phase subtracted from the ESR measurements and from the neutron scattering in magnetic field data11. This mode corresponding to the g -factor g  ~ 1.6–1.7 may be traced up to ω/2π ~ 350 GHz for magnetic field aligned along [110] crystallographic direction1112.…”
mentioning
confidence: 64%
“…Moreover, recent comparative study revealed an excellent agreement between the dispersion laws ω(B ) for the main gapless resonant mode in the AFQ phase subtracted from the ESR measurements and from the neutron scattering in magnetic field data11. This mode corresponding to the g -factor g  ~ 1.6–1.7 may be traced up to ω/2π ~ 350 GHz for magnetic field aligned along [110] crystallographic direction1112. However, the situation with the high-frequency ESR experiments in CeB 6 is more complicated as long as for ω/2π > 200 GHz the second mode with the g -factor g  ~ 1.2–1.3 is observed simultaneously with the main ESR mode1112.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…(4) In unconventional superconductors, a strong magnetic field splits the resonant magnetic exciton mode into two components. This is not the case for CeB 6 , where a second field-induced magnon mode emerges whose energy increases with magnetic field [58]. At the FM zone center (Γ-point) only a single mode is found with a non-monotonic field dependence in phase III.…”
Section: Inelastic Neutron Scattering In Cebmentioning
confidence: 84%
“…The two resonance energies are shown in Figure 6 as a function of magnetic field (figure adapted from Ref. [58]). The splitting is approximately linear in field indicating that it is a Zeeman splitting.…”
Section: Second Resonance At High Fields In Phase II Of Cebmentioning
confidence: 99%